Novel activating mutations lacking cysteine in type I cytokine receptors in acute lymphoblastic leukemia - Shochat, Chen; Bandapalli, Obul Reddy; Kulozik, Andreas; Muckenthaler, Martina (Blood, 2014)
Key Points. Two distinct regions of transmembrane somatic mutations in type I cytokine receptors IL7R and CRLF2 exist in acute lymphoblastic leukemias.Noncyste
Gesehen am 07.08.2020